Assessment of the RIPASA Score in the Diagnosis of Acute Appendicitis in Khartoum State Hospitals, Sudan - Mohammed Hashim Yousif Ahmed; Aamir Abdallah Hamza; Alawia Mohammed Mansour; Khalid Yousif Abuaagla (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2022)
Appendectomy is a common cause of emergency hospitalization, and appendectomy is one of the most common emergency procedures performed in modern medicine. Although it is a common problem, acute appendicitis remains a complex condition to diagnose, especially in the young, the elderly, and women of childbearing age. The aim was to evaluate the accuracy of the RIPASA score for patients with right iliac fossa pain (RIF) and suspected appendicitis. This study is an observational, analytic, and prospective cohort study conducted for one year. All patients suspected of having acute appendicitis and who underwent appendectomy were included in this study. All resected appendages were sent for histological examination. RIPASA scores were calculated for all patients. The study results in the 105 patients studied, 60 (57.1%) were predominantly male. The M/F ratio is 1.3/1. Most of the 98 patients (93.3%) were 40 years old. Most patients had symptoms within 48 hours 79 (75.2%). The most common symptom was anorexia (83.8%). All patients had RIF tenderness (100%). 95 (90.5%) patients had a score >7.5. On gross examination, three patients (2.9%) had a non-inflammatory appendix, 83 patients (79.0%) had a simple inflammatory appendix, the perforated appendix was found in 9 patients (8.6%), appendix mass was found in 6 patients (5,7%), and only four patients (3.8%) had an appendiceal abscess. The appendix was histologically inflamed in 69 patients (65.7%). The sensitivity of the RIPASA scoring system in our study was 69.5%, and the specificity was 70%. The diagnostic accuracy was calculated and was 69.5%. Our study's positive and negative predictive values (PPV, NPV) were 95.7% and 19.4%, respectively. Research conclusion RIPASA value of 7.5 is beneficial and easy to use. Therefore, surgeons can use it as a diagnostic guide for acute appendicitis to reduce the rate of misdiagnosis.